Definition of Intraocular Lens Position after Suture Fixation to the Iris in Remote Post-Op Period with Optical Coherence Tomography - V. N. Nikitin; D. I. Ivanov (Oftalʹmologiâ)
Introduction. Intracapsular IOL position is optimal from optical point of view and in anatomical sense results in formation of a new structure — IOL-capsular bag complex (ICBC). Stable IOL position in post-op period in some cases may be disturbed in some cases due to capsular bag fibrosis or progressive involution zonulolysis against the background of pseudoexfoliation syndrome. The disturbance of correct IOL optic part position (tilt/decentration) results in a decrease of visual acuity and appearance of optic aberrations. ICBC is a dynamic structure from architectonic point of view. Fibrosis of capsular sheets and increase of equatorial cortex (Zommering ring) may result to IOL shift in long term post-op period. Accurate definition of these parameters is crucial for estimation of impact on visual functions. The existing methods of IOL position definition are based on various principles, therefore, it is not correct to compare the parameters obtained with various devices.Pursope. To develop a method of IOL tilt and decentration definition with optical coherence tomography (Optovue, AS-OCT) and to define these parameters after suture fixation of IOL-capsular bag complex to the iris in remote post-op period.Methods. The parameters of 50 eyes operated from 2014 to 2016 for ICBC dislocation were estimated. The patients were examined again in 5 years or later. Definition of IOL position was performed with optical coherence tomography (Optovue, ASOCT) using Cornea Crossline protocol. For estimation of obtained parameters and their deviation from normal the study group was compared with a control group of 30 pseudophakic eyes with high uncorrected visual acuity.Results. In the study group the following data was obtained. Mean value of IOL tilt angle was 3.02 ± 2.04° in the horizontal meridian and 2.39 ± 1.4° in the vertical meridian. Decentration from the center of non-mydriatic pupil was 396 ± 222 microns in the horizontal meridian and 455 ± 278 microns in the vertical meridian. In the control group mean value of IOL tilt angle was 3.04° ± 1.28° in the horizontal meridian and 1.43° ± 0.53° in the vertical meridian. Decentration from the center of non-mydriatic pupil was 190 ± 114 microns in the horizontal meridian and 259 ± 108 microns in the vertical meridian. The difference between the groups is statistically significant (p < 0,05).Conclusion. The developed method allows non-contact definition of IOL position (tilt/decentration) with optical coherence tomography (Optovue, AS-OCT). The obtained data shows stable correct frontal position of IOL optic part in remote post-op period after suture fixation of ICBC to the iris.